Composition dependence of photoluminescence properties of poly(9, 9-di-n-hexylfluorenyl-2, 7-diyl) with perovskite-structured SrTiO3 nanocomposites. (May 2016) - Din, U.K.N.; Salleh, M.M.; Aziz, T.H.T.; Umar, A.A.
Abstract: Nanocomposite thin films of poly(9, 9-di- n -hexylfluorenyl-2, 7-diyl) (PHF) with 10–50 wt% perovskite-structured SrTiO3 nanoparticles (designated as PHF:SrTiO3 ) were prepared by spin coating. The photoluminescence (PL) properties of the nanocomposites thin films were studied. The incorporation of SrTiO3 nanoparticles into the nanocomposite thin films enhanced the original PL intensities of the host PHF thin films. The intensities of the PL peak for the nanocomposite thin films were dependent on the amount of SrTiO3 nanoparticles in the films and the homogeneity of the nanoparticle distribution. The distribution of the SrTiO3 nanoparticles contributed to the overlapping molecular orbital sites in PHF:SrTiO3, which promoted the excited electrons from the conduction band of SrTiO3 transferred to the excited energy level of the PHF host material. In this case, the perovskite-structured SrTiO3 nanoparticles act as sensitizers. Highlights: The incorporation of perovskite-structured SrTiO3 nanoparticles into the nanocomposite thin films enhanced the original PHF PL intensities. The PL peak intensities for the nanocomposite thin films were dependent on the amount of SrTiO3 nanoparticles in the films. The homogeneity of the SrTiO3 nanoparticles distribution in the films effect the PL intensity peak.